Interpersonal Attraction as a Basis of Informal Organization: Comment and Review - Bell, Robert R.; Mascaro, Guillermo F. (Academy of Management Journal, 1972)
The article discusses research on the formation of informal groups based on attraction in response to the article “Interpersonal Attraction as a Basis of Informal Organization,” featured in a previ...